Frequency of Contrast Induced Nephropathy in Diabetic Patients Undergoing Coronary Angioplasty - Zahoor Ahmad Khan, Ahmad Ali Khan, Salman Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out the frequency of contrast induced nephropathy in diabetic patients undergoing coronary angioplasty. Material and Methods: After approval from the Hospital ethical committee, the study was conducted in the department of cardiology Hayatabad medical complex Peshawar from 28th July 2020 to 28th January 2021. A total of 136 patients were followed in this study. Oral anti-glycemic agents (metformin) were stopped before and after two days of cardiac catheterization. Previous medical record was checked including renal profile. Phlebotomist was called to take blood for random blood sugar, HbA1C level and renal functions tests (RFTs). Angioplasty was performed according to the set protocol. Serum creatinine level was checked both pre and post contrast. Results: Our study included 136 individuals, with a median age of 48 (+13.36), and we found that 59% of them were men and 41% were women. Of the 136 individuals, only 7 (5%) had contrast-induced nephropathy. Conclusion: To sum up, we found that five percent of diabetic patients having coronary angioplasty in a tertiary care hospital in Peshawar had contrast-induced nephropathy. Keywords: Diabetes mellitis, Coronary angioplasty, Contrast-induced nephropathy.